The Relationship of HbA1c Levels and Degree of Diabetic Nephropathy in Patients with Type 2 Diabetes Mellitus in RSI Jemursari Surabaya - Shofiyah, Putri Dhiya Ayu; Shanty, Lea Maera; Lestari, Marselli Widya (UNUSA Press, 2025)
Introduction: Type 2 diabetes mellitus is a metabolic disorder frequently associated with long-term complications. One of the most common microvascular complications is diabetic nephropathy, a condition that significantly contributes to morbidity and mortality among patients. A reduced glomerular filtration rate (GFR) reflects a more advanced stage of nephropathy, and when accompanied by elevated HbA1c levels, it indicates poor glycemic control and a greater risk of diabetes-related complications. Objective: To prove the relationship between HbA1c levels and the degree of diabetic nephropathy Methods: This study is an analytical observational research with a cross-sectional approach. The population in this study consists of medical record data from patients with type 2 diabetes mellitus at RSI Jemursari, totaling 946 patients. The sample was obtained using the Slovin formula, with a 10% margin of error, resulting in 90 samples. Sampling was done using the nonprobability sampling method of consecutive sampling. The statistical test uses the Spearman test in SPSS. Results: The significance value was <0.001 (<0.1), and the correlation coefficient was 0.416. The results of the Spearman statistical test demonstrate a significant relationship between the two variables, with a moderate quality of the relationship between them. Conclusions: A significant relationship was found between the HbA1c level variable and the degree of nephropathy in patients with type 2 diabetes mellitus, characterized by a correlation coefficient indicating a moderate quality of relationship.